Environmental monitoring using drone images and convolutional neural networks - Thomazella, R.; Castanho, J. E.; Dotto, F. R.L.; Rodrigues Júnior, O. P.; Rosa, G. H.; Marana, A. N.; Papa, J. P. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Recently, drone images have been used in a number of applications, mainly for pollution control and surveillance purposes. In this paper, we introduce the well-known Convolutional Neural Networks in the context of environmental monitoring using drone images, and we show their robustness in real-world images obtained from uncontrolled scenarios. We consider a transfer learning-based approach and compare two neural models, i.e., VGG16 and VGG19, to distinguish four classes: water, deforesting area, forest, and buildings. The results are analyzed by experts in the field and considered pretty much reasonable.
Keywords: Convolutional Neural Networks; Drones; Land-use classification